A study of the significance of the Australian historical novel in the period of the History Wars, 1988 - present - Jones, Joanne (Curtin University, 2012)
Australian historical novels and the History Wars (1998-2008). The period of recent Australian cultural history known as the History Wars was of unprecedented significance in reshaping the relationship between the nation and its colonial past. While much of this cultural “backtracking” (Collins and Davis) was due to the groundbreaking and politically efficacious work of revisionist historians, an assessment of the role played by historical fiction during this time of unsettling and “hidden” histories is due.This thesis takes the publically-waged debate over the suitability of novelists to render authoritative versions of significant events or periods as its starting point. From there, however, it delves deeper into the politics of form, analysing the connection between the realist modes of traditional, empiricist histories and the various explorations of the colonial past that have been figured through different historical novels. The forms of these novels range from classic realism to frontier Gothic, various Romanticisms, magical realism, and reflexive post-modernism. In particular, I investigate the relationship between politics and form in Rodney Hall’s Captivity Captive (1988), David Malouf’s Remembering Babylon (1993), Kim Scott’s Benang (1999), Richard Flanagan’s Gould’s Book of Fish (2003), and Kate Grenville’s The Secret River (2005) and The Lieutenant (2008).The relative formal freedoms offered through historical novels offer the chance to confront the past in all of its contradiction and complexity. The terrain of the postmodern and historical sublime — of loss and uncertainly— is one in which historical fiction can perform an important political and ethical role. The immeasurably vast space which lies beyond history, that space of those who are often unrepresented, often victims, often silent, is an abyss into which fiction, particularly historical fiction, is able imaginatively and ethically to descend.